GAMIFICATION CONCEPT WITHOUT DIGITAL PLATFORMS: A STRATEGY FOR PARENTS ON MOTIVATING CHILDREN STUDY AT HOME DURING COVID-19 PANDEMIC - Zamzami Zainuddin; Cut Muftia Keumala (Nurul Jadid University, 2021)
The temporary closure of schools around the world to limit the spread of the COVID-19 has induced a new challenge for parents. Particularly, for those working remotely, making sure the children follow the learning schedule given by the school and keeping them occupied at home until bedtime is no obvious duty to make efforts to boost their enthusiasm. Therefore, one strategy proposed to motivate children's learning at home is to gamify their learning activities. Numerous studies have been published on the use of various digital platforms in gamification research, however, gamified systems in a non-technology environment or non-digital platform have been inadequately discussed and investigated by scholars. Thus, in this study, we will present a concise discussion on how gamified activities can be utilized in a non-tech environment. This conceptual paper employing a systematic literature review in collecting and analyzing the data. Through a review of the current empirical and conceptual literature, this study presents a new conceptual framework of the gamification concept in a non-technology environment. The study recommends that applying game-based elements or mechanics to motivate and engage children's learning can be carried out anywhere and anytime for any grade level, without waiting for high-tech supports.